Snakebites and the Effect of Serum Anti Bisa Ular (SABU) Antivenom at Dr. Hasan Sadikin General Hospital Bandung, Indonesia: an Overview Period 2015–2019 - Sharon Noor Alya; Achadiyani Achadiyani; Muhammad Hasan Bashari; Hardisiswo Soedjana; Enny Rohmawaty (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Snakebite is considered a global health issue, especially in the Southeast Asian region. However, data regarding snakebite cases in Indonesia are still very limited. This study aimed to explore the venomous snakebite cases and the serum anti bisa ular (SABU) antivenom effect in treating venomous snakebite caused by other than the snake species indicated in currently available SABU antivenom formulas.Methods: The analytical descriptive method with a cross-sectional study design was conducted in 2021 using a total sampling from the medical records of 63 patients diagnosed with snakebite at Dr. Hasan Sadikin General Hospital Bandung from 2015 to 2019. Characteristics of patients, clinical manifestation, and correlation between snakes species and outcomes after treatment with or without administration of SABU antivenom were collected.Results: Out of 63 patients, males (79%) were predominant with an average age of 39 years. Fifty-six patients arrived at the Emergency Room less than 24 hours after the occurrence (89%). Most cases were categorized as grade 2 (41.%) where the upper extremities were commonly bitten the body area (64%). Edema (83%) was the most common manifestation. There was no correlation between snake antivenom administered to a specific snake species and the stated outcome (p=0.053), meaning that SABU antivenom might be an effective alternative to treat more types of snakebites.Conclusions: Snakebites are most common in males, attack the upper extremities, categorized as grade 2 with edema. Administration of SABU antivenom provides the similar outcome compared to the group caused by the Javan spitting cobra, Banded krait, and Malayan pit viper.